Insulin promotes T cell recovery in a murine model of autoimmune myocarditis. (3rd December 2012) - Zhang, Y.; Zhuang, R.; Geng, C.; Cai, X.; Lei, W.; Tian, N.; Gao, F.
Summary Glucose‐insulin‐potassium (GIK) is a useful adjunct to myocarditis. Besides its essential action in energy metabolism, insulin also exerts an anti‐inflammatory effect. This study investigated the effect of insulin on myocardial inflammation in experimental autoimmune myocarditis (EAM) in mice and its potential role in T cell regulation. Mice were divided randomly into a normal control group, a saline‐treated EAM group and an insulin‐treated EAM group. The histopathological changes of myocardium, α‐myosin heavy chain (MyHCα)614–629 antigen‐specific autoantibody titre, the serum level of cardiac troponin I (cTnI), mitogen‐activated protein kinase (MAPK) family members' activity and content were measured. Furthermore, the phenotype of T lymphocyte subsets in splenocytes was analysed to evaluate the immune status of mice. Insulin reduced serum cTnI of EAM mice on days 14 and 21 (P < 0·05) after immunization, with no changes in blood glucose and autoantibody production. Western blot revealed that extracellular signal‐regulated protein kinase (ERK1/2) may be a determining factor in this process. Total ERK1/2 and phospho‐ERK1/2 (p‐ERK1/2) were both up‐regulated in insulin‐treated mice after immunization. We also found that insulin treatment promoted T cell recovery without changing the naive‐to‐memory T‐cell ratio; in particular, CD3+ T cells in insulin‐treated mice proliferated more vigorously than in control mice (P < 0·05). We report here for the first time that insulin alleviates myocarditis in the EAM model. These data show that insulin has a direct effect on T cell proliferation in EAM. It is possible that GIK or insulin may assist T cell recovery towards normal in myocarditis, especially for diabetic or hyperglycaemic patients.